Fatal Cerebral Malarial in a Burn Patient - A Case Report - P K Sharma; D S Badkur; S M Tamaskar (Indian Journal of Plastic Surgery)
A 25 year old male with 50% burns died on the 10th post burn day due to cerebral malaria. The clinical features and post mortem findings are described. The need to think of another cause for symptoms which appear like septicaemia particularly in an unresponsive patient is emphasised.